Early or deferred initiation of efavirenz during rifampicin‐based TB therapy has no significant effect on CYP3A induction in TB‐HIV infected patients. (7th December 2020) - Aklillu, Eleni; Zumla, Alimuddin; Habtewold, Abiy; Amogne, Wondwossen; Makonnen, Eyasu; Yimer, Getnet; Burhenne, Jürgen; Diczfalusy, Ulf
Abstract : Background and Purpose: In TB‐HIV co‐infection, prompt initiation of TB therapy is recommended but anti‐retroviral treatment (ART) is often delayed due to potential drug–drug interactions between rifampicin and efavirenz. In a longitudinal cohort study, we evaluated the effects of efavirenz/rifampicin co‐treatment and time of ART initiation on CYP3A induction. Experimental Approach: Treatment‐naïve TB‐HIV co‐infected patients ( n = 102) were randomized to efavirenz‐based‐ART after 4 ( n = 69) or 8 weeks ( n = 33) of commencing rifampicin‐based anti‐TB therapy. HIV patients without TB ( n = 94) receiving efavirenz‐based‐ART only were enrolled as control. Plasma 4β‐hydroxycholesterol/cholesterol (4β‐OHC/Chol) ratio, an endogenous biomarker for CYP3A activity, was determined at baseline, at 4 and 16 weeks of ART. Key Results: In patients treated with efavirenz only, median 4β‐OHC/Chol ratios increased from baseline by 269% and 275% after 4 and 16 weeks of ART, respectively. In TB‐HIV patients, rifampicin only therapy for 4 and 8 weeks increased median 4β‐OHC/Chol ratios from baseline by 378% and 576% respectively. After efavirenz/rifampicin co‐treatment, 4β‐OHC/Chol ratios increased by 560% of baseline (4 weeks) and 456% of baseline (16 weeks). Neither time of ART initiation, sex, genotype nor efavirenz plasma concentration were significant predictors of 4β‐OHC/Chol ratios after 4 weeks of efavirenz/rifampicin co‐treatment. Conclusion and Implications: Rifampicin induced CYP3A more potently than efavirenz, with maximum induction occurring within the first 4 weeks of rifampicin therapy. We provide pharmacological evidence that early (4 weeks) or deferred (8 weeks) ART initiation during anti‐TB therapy has no significant effect on CYP3A induction. LINKED ARTICLES: This article is part of a themed issue on Oxysterols, Lifelong Health and Therapeutics. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.16/issuetoc